A case analysis of securing organisations against information leakage through online social networking - Abdul Molok, Nurul Nuha; Ahmad, Atif; Chang, Shanton (Elsevier, 2018)
The inadvertent leakage of sensitive information through Online Social Networking (OSN) represents a significant source of security risk to organisations. Leakage of sensitive information such as trade secrets, intellectual property and personal details of employees can result in a loss of competitive advantage, loss of reputation, and erosion of client trust. We present 4 case studies which examine drivers for employee leakage behaviour and corresponding security management strategies. Drawing on these case studies, we present a maturity framework for organisational OSN Leakage Mitigation Capability (OSN-LMC) and lessons learned from the case analysis.